Brain Computer Interface and Brain Centrism: Origins, Challenges, and Reflections - Shaoqing MA; Gaofeng WANG (Yixue yu zhexue, 2025)
The continuous breakthroughs in brain computer interfaces (BCI) have once again brought attention to the central role of the brain from a technological perspective. Through BCI, the viewpoint of brain centrism has re-emerged in academic discourse. The formation of brain centrism originates from the philosophical tradition of metaphysics and has formed a hierarchical structure of "brain-technology-body". As a technological mediator, BCI reconciles the contradictions between humans and technology, and has seemingly infinite development possibilities. However, upon closer analysis, brain centralism encounters significant challenges from both material and spiritual practices rooted in bodily existence. After analyzing the theory of brain centrism and its related physical and technological factors through the phenomenological theory of Stigler's technique, it is found that brain centrism lacks a reliable theoretical and practical basis. Therefore, it is necessary to understand brain centrism from an objective and scientific perspective, fully recognizing the importance of the brain and acknowledging the significance of factors such as the body and society.